2004
DOI: 10.2174/0929867043364252
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Conformationally Constrained Calcitonin (Ct) Analogs to the Understanding of the Structural and Conformational Requirements of Calcitonin Bioactivity and to the Design of Potent Agonists

Abstract: Restricting the conformational flexibility of medium-sized linear polypeptides is a valuable approach to identify and characterize the structural and conformational features that define their biological activities and to design analogs with enhanced agonistic or antagonistic properties and with potential therapeutic applications. The calcium-regulating and bone resorption-inhibiting hormone calcitonin (Ct) is a conformationally flexible polypeptide of 32 amino acid residues that has long been applied therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
(296 reference statements)
0
3
0
Order By: Relevance
“…Relatively little is known about structure–activity relationships for IAPP’s normal biological action in comparison to its pathological aggregation. Experiments on truncated versions of calcitonin and CGRP (the closest homologue of IAPP) have shown that the formation of the amphipathic helix is sufficient for receptor binding but activation of the receptor requires the N-terminal ring 66. Removal of the N-terminal ring or reduction of the disulfide bridge results in CGRP binding to its receptor in an inactive conformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively little is known about structure–activity relationships for IAPP’s normal biological action in comparison to its pathological aggregation. Experiments on truncated versions of calcitonin and CGRP (the closest homologue of IAPP) have shown that the formation of the amphipathic helix is sufficient for receptor binding but activation of the receptor requires the N-terminal ring 66. Removal of the N-terminal ring or reduction of the disulfide bridge results in CGRP binding to its receptor in an inactive conformation.…”
Section: Discussionmentioning
confidence: 99%
“…All of the peptides in this family possess an amidated C-terminus, an amphipathic helix near the N-terminus, a largely disordered C-terminus, and an N-terminal ring connected by a disulfide bond. Two binding sites have been proposed for the binding of peptides of this family to the membrane-bound receptor: one near the membrane surface that would be consistent with the orientation found in this study for rIAPP and another requiring a more deeply inserted membrane orientation as found for hIAPP 1−19 and hypothesized for hIAPP. ,, Relatively little is known about structure−activity relationships for IAPP’s normal biological action in comparison to its pathological aggregation. Experiments on truncated versions of calcitonin and CGRP (the closest homologue of IAPP) have shown that the formation of the amphipathic helix is sufficient for receptor binding but activation of the receptor requires the N-terminal ring . Removal of the N-terminal ring or reduction of the disulfide bridge results in CGRP binding to its receptor in an inactive conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation